Becoming Calder - Sheridan, Mia (Naperville : Sourcebooks, 2023)
"The first book in the Acadia Duology, a forbidden friends-to-lovers romance, from the New York Times bestselling author of Archer's Voice. The light of love has always found its way into even the darkest of places, from the beginning of time to the end of the world. There is a place in today's America with no electricity, no plumbing, and no modern conveniences. In this place, there is no room for dreams, no space for self-expression, and no tolerance for ambition. In the community of Acadia lives a boy named Calder with the body of a god and the heart of a warrior. He serves his family with faith and honor, but he dares to dream of more...especially when an angel-faced girl his age is brought to their community. To Acadia, Eden is obedient perfection, prophesized to lead them to eternal peace, but to Calder, even at first glance, she is so much more. Calder and Eden were never meant to be friends. Certainly never meant to fall in love. After all, Eden is betrothed to Acadia's leader, secluded until the day of her destiny. But as she and Calder steal fleeting moments and forbidden kisses, their hearts grow dangerously tangled, and it's too late to heed the warnings. In Acadia, they can never be together. But Acadia is all they know. If they want any chance at a future, they must risk everything to choose between the life they were taught to live and the dream their hearts want to follow"--